Purificação e caracterização de uma xilanase produzida por Streptomyces thermocerradoensis crescido em farelo de trigo como fonte de carbono - Ticona, Alonso Roberto Poma (2015)
The genus Streptomyces is present in nature, preferably in soils rich in organic detritus and grow into microcolonies may degrade biopolymers such as lignocellulosic biomass (due to the production of xylanases, cellulases, pectinases, mannanases). Xylanases act in the degradation of plant cell wall hemicellulose and have many applications in industrial processes. In this work, Streptomyces thermocerradoensis was cultivated for 4 days on two sources of carbon: Sugarcane bagasse (SCB) and wheat bran (WB). The isolate of S. thermocerradoensis was able to produce xylanase in the two sources of carbon. However, the highest production was observed in WB and enzyme produced under these conditions was used for purification and characterization. The crude extract obtained was concentrated by precipitation with ammonium sulfate. The concentrated fraction was purified by chromatography ANX Sepharose (pH 8.0) and CM-Sepharose cation exchange (pH 4.0) with a molecular mass of 33 kDa. The xylanase showed optimal activity at 50 °C and pH 5.0. The enzyme activity was strongly inhibited in the presence of Hg2+, Ag2+, Fe3+ and increased their activity in the presence of Co2+, Ca2+ and Mn2+. The thermostability was kept at 80% for 2 hours at a temperature of 40 to 50 °C. The parameters Km and Vmáx for oat spelt xylan was 3,5 mg.mL-1 and 0,5955 μmol.min-1, respectively.